2019
DOI: 10.29021/spdv.77.1.984
|View full text |Cite
|
Sign up to set email alerts
|

Harlequin Ichthyosis: Case Report

Abstract: Harlequin ichthyosis is a rare autosomal recessive congenital disease in which neonates present generalized hyperkeratotic plaques and deep fissures, ectropion, eclabium, malformation of the auricular pavilion and typical facies. Although several complications related to the skin restriction may occur, support in intensive care and early introduction of systemic retinoids, such as acitretin, have significantly contributed to patients' survival and improved prognosis. The purpose of this report is to present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In such cases, it is plausible that the disorder may be attributed to a novel dominant mutation (8). The subsequent pregnancy is associated with an approximate recurrence incidence of 25% (9). Within the scope of our study, two cases were found to have a family history.…”
Section: Discussionmentioning
confidence: 77%
“…In such cases, it is plausible that the disorder may be attributed to a novel dominant mutation (8). The subsequent pregnancy is associated with an approximate recurrence incidence of 25% (9). Within the scope of our study, two cases were found to have a family history.…”
Section: Discussionmentioning
confidence: 77%
“…The recurrence of this condition in the subsequent pregnancy is estimated to be 25%. 6 Hence, it is crucially important to counsel the parents regarding the genetic disorder and its probability of their next conception.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the young mother presented with obstetric pain and preterm premature rupture of the membrane as an obstetric emergency and cesarean delivery was performed. The recurrence of this condition in the subsequent pregnancy is estimated to be 25% 6 . Hence, it is crucially important to counsel the parents regarding the genetic disorder and its probability of their next conception.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence of this condition in the subsequent pregnancy is estimated to be 25%. 6 Hence, it is crucially important to counsel the parents regarding the genetic disorder and its probability in their next conception.…”
Section: Discussionmentioning
confidence: 99%